Answer:
1/5 = 0.2 so, she can drink 0.1 of a gallon each day
to turn a fraction into a decimal you should do..
1/5 since 5 can't go into 1 you add a 0 to the 1 making it a 10 and move the decimal point, since 5 goes into 10, 2 times, we get 0.2
The smaller triangle was dilated to form the larger triangle. What is the value of x? A smaller triangle has side lengths of 3 and 5. A larger triangle has side lengths of 9 and x + 1. 10 11 14 15
Answer:
14 is the answer
Step-by-step explanation:
I hope I helped
The value of x is 14.
The correct option is C.
What is ratio?The ratio is a numerical relationship between two values that demonstrates how frequently one value contains or is contained within another.
Given:
The smaller triangle was dilated to form the larger triangle.
A smaller triangle has side lengths of 3 and 5.
A larger triangle has side lengths of 9 and x + 1.
That means,
the ratio,
3/5 = 9/(x + 1)
3x + 3 = 45
x = 14
Therefore, the value is 14.
To learn more about the ratio;
https://brainly.com/question/13419413
#SPJ6
I need some help on solving this problem
Answer:
J. 80°
Step-by-step explanation:
I NEED HELP!!!! WITH NUMBER 9, & 10??
Answer:
awnser one is 7 and question 2 is -10
Step-by-step explanation:
−12−2−−55=? question one
In the first fraction, the negative numerator and negative denominator cancel each other.
Since the the second fraction is negative and you are subtracting, remove the negative sign and switch the operation to addition.
The equivalent equation is
122+55=?
The fractions have unlike denominators. First, find the Least Common Denominator and rewrite the fractions with the common denominator.
LCD(12/2, 5/5) = 10
Multiply both the numerator and denominator of each fraction by the number that makes its denominator equal the LCD. This is basically multiplying each fraction by 1.
(122×55)+(55×22)=?
Complete the multiplication and the equation becomes
6010+1010=?
The two fractions now have like denominators so you can subtract the numerators.
Then:
60+1010=7010
Since 70 divided by 10 equals 7 then,
7010=7
Therefore:
−12−2−−55=7
Question 2
−81+6−3=?
In the second fraction, move the negative sign from the denominator to the numerator and the value remains the same.
The equivalent equation is
−81+−63=?
The fractions have unlike denominators. First, find the Least Common Denominator and rewrite the fractions with the common denominator.
LCD(-8/1, -6/3) = 3
Multiply both the numerator and denominator of each fraction by the number that makes its denominator equal the LCD. This is basically multiplying each fraction by 1.
(−81×33)+(−63×11)=?
Complete the multiplication and the equation becomes
−243+−63=?
The two fractions now have like denominators so you can add the numerators.
Then:
−24+−63=−303
Since -30 divided by 3 equals -10 then,
−303=−10
Therefore:
−81+6−3=−10
Solution by Formulas
Apply the fractions formula for addition, to
−81+6−3
and solve
(−8×−3)+(6×1)1×−3
=24+6−3
=30−3
=−10
NEED THIS ANSWER BY THE END OF THE DAY PLEASE HELP !!
A party rental company has chairs and tables for rent. The total cost to rent 5 chairs and 3 tables is $32. The total cost to rent 2 chairs and 12 tables is $83. What is the cost to rent each chair and each table ?
Answer: So the cost to rent each chair is $1.25 and the cost to rent each table is $8.50
Step-by-step explanation:
Let C = cost to rent each chair
Let T = cost to rent each table
4C + 8T = 73
2C + 3T = 28
Multiply the 2nd equation by (-2) and then add the equations together
4C + 8T = 73
-4C - 6T = -56
2T = 17
T = 17/2 = 8.5
Plug this in to the 1st equation to solve for C
4C + 8(17/2) = 73
4C + 68 = 73
4C = 5
C = 5/4 = 1.25
solve for u
Simplify your answer as much as possible.
Simplify the following by combining like terms:
-5- x+4x - 4
4x + 2y = 12
what's the y intercept
What is the absoulte valve of I -32i
Answer:
32
Step-by-step explanation:
Absolute value is always positive.
Forget that last one I posted I need this pls
SOMEONE HELP WITH THIS NOW FOR BRAINLIEST
Answer:
The two lines intersect at (6, -4) which is the solution to this system of equations.
x = 6
y = -4
[tex]\left \{ {{-3x-9y = 18} \atop {4x+3y=12}} \right.[/tex] can be rewritten as [tex]\left \{ {{y=-\frac{1}{3}x-2 } \atop {y=-\frac{4}{3}x+4 }} \right.[/tex] to make graphing easier.
ASAPPP
what is the domain and range?
Answer:
domain refers to the set of possible input values, the domain of a graph consists of all the input values shown on the x-axis. The range is the set of possible output values, which are shown on the y-axis
PLEASE ANSWER!! WILL MARK BRAINLIEST
Expand & simplify
5
(
p
+
6
)
−
5
(
p
−
2
)
Answer:
Expanded form - write 5 ( p+6 ) - 5 ( p - 2)
as an equation y = 5 (p+6) -5(p-6)
simplifyed form - 40
Step-by-step explanation
A circle is tangent to the line given by the equation 3x-y= 15 at the point (9,12). The center of the radius falls on the line given by 2y+x=8. Find the equation of the circle and identify its center and radius
Answer:
The equation of the circle is x² + y² + 12x - 14y - 165 = 0 , its center is (-6, 7) and its radius is 5√10 units.
Step-by-step explanation:
a. The center of the circle
Since the equation of the tangent of the circle is 3x - y = 15, we write it in standard form. So y = -3x - 15. Its gradient is -3. The perpendicular line tot he tangent is the radius and it passes through the center of the circle and the point (9, 12). For two perpendicular lines of gradient m₁ and m₂, m₁m₂ = -1. If m₁ = -3, then m₂ the gradient of our radius line is gotten from m₁m₂ = -1
m₂ = -1/m₁ = -1/-3 = 1/3
Since the radius also passes through the point (9, 12), its equation is gotten from
(y - y₁)/(x - x₁) = m₂ where (x₁, y₁) = (9, 12)
Substituting the value of the variables into the equation, we have
So, (y - 12)/(x - 9) = 1/3
cross-multiplying, we have
3(y - 12) = (x - 9)
expanding the brackets, we have
3y - 36 = x - 9
collecting like terms, we have
3y = x - 9 + 36
3y = x + 27
So, the equation of the radius line is
3y - x = 27.
Now, since the center of the circle lies on the line 2y + x = 8, the radius line and this line intersect at the center of the circle. So, we solve both equations simultaneously to find the center of the circle.
So, 3y - x = 27 (1)
2y + x = 8 (2)
adding (1) and (2), we have
5y = 35
y = 35/5
y = 7
Substituting y = 7 into (2), we have
2y + x = 8
2(7) + x = 8
14 + x = 8
x = 8 - 14
x = -6
So, the center of the circle is at (-6, 7)
b. The radius of the circle
The radius of the circle is the length of the line from the tangent point to the center of the circle. So, r = √[(x₂ - x₁)² + (y₂ - y₁)²] where (x₁, y₁) = (-6, 7) and (x₂, y₂) = (9, 12).
Substituting these into r, we have
r = √[(9 - (-6))² + (12 - 7)²]
= √[(9 + 6)² + (12 - 7)²]
= √[15² + 5²]
= √[225 + 25]
= √250
= √25 × √10
= 5√10 units
c. The equation of the circle
Now, the equation of a circle with center (h,k) and radius, r is
(x - h)² + (y - k)² = r² where (h. k) = (-6,7)
Substituting the variables into the equation, we have
(x - (-6))² + (y - 7)² = (√250)²
(x + 6)² + (y - 7)² = 250
expanding the brackets, we have
x² + 12x + 36 + y² - 14y + 49 = 250
collecting like terms, we have
x² + y² + 12x - 14y + 36 + 49 - 250 = 0
x² + y² + 12x - 14y - 165 = 0
So, the equation of the circle is x² + y² + 12x - 14y - 165 = 0 , its center is (-6, 7) and its radius is 5√10 units.
What is X and Y ? I’ll give brainliest!
Answer:
I think X is 45 degrees and y is 75 degrees if not right just dont give brainly or mark it stars 1 sorry if this was no help...
Step-by-step explanation:
I need help please..
Angle PQR is a straight angle.
The measure of angle SQR is 25°.
The measure of angle PQS is xº.
What is the value of x?
Answer:
x=155
Step-by-step explanation:
since its a straight line, it has to equal 180 in total.
SQR is 25, so to find PQS you subtract 180-25
Which equals 155
Find the distance between the two points in simplest radical form.
(8, -3)(6, -8)
Answer:
sqrt(29)
Step-by-step explanation:
distance = sqrt√( (x2 - x1)^ + (y2 - y1)^2 )
x1 = 6
x2 = 8
y1 = -8
y2 = -3
distance = sqrt( ( 8 - 6)^2 + (-3 - -8)^2 )
distance = sqrt( 2^2 + 5^2)
distance = sqrt(29)
Answer:
29
Step-by-step explanation:
29
(x^3 + 8x^2 + kx + 4) ÷ (x+ 2)
Please help how do i solve for k please include steps this is called remainder theorem
Answer: 14
Step-by-step explanation:
Check it
Answer:
k = 14
Step-by-step explanation:
The Remainder theorem states that if f(x) is divided by (x + h) then the remainder is f(- h)
If (x + h) is a factor of f(x) then the remainder is zero, that is f(- h) = 0
Given (x + 2) is a factor of f(x) then f(- 2) = 0, that is
(- 2)³ + 8(- 2)² - 2k + 4 = 0
- 8 + 8(4) - 2k + 4 = 0
- 8 + 32 - 2k + 4 = 0
- 2k + 28 = 0 ( subtract 28 from both sides )
- 2k = - 28 ( divide both sides by - 2 )
k = 14
im so confused please help
Answer:
9
Step-by-step explanation:
It's just telling you that the value of x is 3, so in the equation,
you replace x with 3,
2(3) + 3,
2 x 3 = 6,
6+ 3 = 9
Answer:
9
Step-by-step explanation:
They give you the equation:
2x+3
And they give you the (x):
x=3
So you simply replace (x) with 3
2x+3
2(3)+3
now solve
2•3= 6
6+3 = 9
9 is your answer.
Hope this helps! If you have any questions on how I got my answer feel free to ask. Stay safe!
I need ur help ASAP plsssssss first right answer gets brainliest
Answer:
21
Step-by-step explanation:
If your cell phone bill is $85.87 and there is a 8.4% late fee, how much will your bill be if it's late?
Answer:
Step-by-step explanation:
If you're late on your cell phone bill, you'll generally be fined as much as 5 percent of the amount due or $5, whichever is higher. Late charges may not kick in immediately. At AT&T, for example, the fee is applied six days after your due date. Often, your late fee will be subject to taxes.
Answer:
7.21308 is the late fee so in total it is going to be 98.08308
Step-by-step explanation:
Your welcome
HURRY!!! Please tell me a awnser i can just pick them in my class pick from the bottem
Answer:
#5 the slope is 1/2
#6 the slope is -5/4
Step-by-step explanation:
Given y = (2x + 3)2, choose the standard form of the given quadratic equation. 0 = 25x2 0 = 4x2 + 9 0 = 4x2 + 10x + 6 0 = 4x2 + 12x + 9 Identify the values of a, b, and c. a = b = c =
Answer:0=4x^2+12x+9
Step-by-step explanation:
The standard form of the quadratic equation is y = 4x² + 12x + 9. Then the correct option is D. And the value of a, b, and c will be 4, 12, and 9.
What is a quadratic equation?The quadratic equation is given as ax² + bx + c = 0. Then the degree of the equation will be 2. Then we have
The equation is given below.
y = (2x + 3)²
Simplify the equation, then we have
y = 4x² + 12x + 9
Then the correct option is D.
Compare the equation with standard equation, then we have
a = 4
b = 12
c = 9
More about the quadratic equation link is given below.
https://brainly.com/question/2263981
#SPJ2
A triangle has sides with lengths of 6 centimeters, 5 centimeters, and 3 centimeters. Is it a right triangle?
Answer:
No
Step-by-step explanation:
A triangle with a side of five is only a perfect right triangle when it's in a 5,12,13 ratio.
Furthermore, to check, 5^2 is 25 and 3^2 is 9. 25+9 is 34, which doesn't not have a square root of 6.
Lizet bought a bag of gummy bears and ate one-third of them. The next day, she ate 16 more gummy bears. If she ate a total of 37 gummy bears, how many were originally in the bag?
Answer:
im trying to figure out the same thing
Step-by-step explanation:
What is the slope-intercept form of the linear equation 2x + 3y = 6? Drag and drop the appropriate number, symbol, or variable to each box.
Answer:
[tex]y=-\frac{2}{3}x+2[/tex]
Step-by-step explanation:
y = -2/3 x + 2
Answer:y=-2/3x+2
Step-by-step explanation:
Trust me
A salespersons commision varies directly with their sales. For $1000 in sales, the commission is $85. What is the constant of variation? What is the commission for $2300 in sales?
PLEASE HELP ME
7. George placed the numbers -1/2 , 0.2 , 8/9 on the number line. Which of the numbers is furthest from zero?
A: -1/2
B: 0.2
C: 8/9
Does the following mapping diagram represent a function?
A. YES
B. NO
C. NOT ENOUGH INFORMATION
Answer:
a
Step-by-step explanation:
Help
Help help pls I can’t answer this
Answer:
A
Step-by-step explanation:
1/6^2 =
1/36
Answer:
B
Step-by-step explanation:
When you divide 2 numbers with the same base, you subtract the exponents. We know fractions are basically division, so we would do 3-5. You get -2 as your exponent and we know negative exponents can be written two ways: [tex]6^{-2} and \frac{1}{x6^{2} }[/tex]. Both of those are there, so they are not the correct answer. B can be determined as the one not because the exponent is positive.